Central venous access through the external jugular vein in children submitted to bone marrow transplantation - Godoy,José Luiz de (2005)
Establishment of long-term central venous access is a sine qua non step for bone marrow transplantation in children. Most frequently, long-term central venous access has been obtained via blind percutaneous cannulation of subclavian and internal jugular veins or via internal jugular vein cutdown. In order to avoid some potential minor and major complications associated with the subclavian or internal jugular approaches, the authors describe an easy, simple and safe method for central venous access through an external jugular vein cutdown that should be of interest to readers involved in the field of bone marrow transplantation. It should be also considered for children as well as adults needing central venous access via an external catheter - or totally implantable port - for reasons other than bone marrow transplantation, such as total parenteral nutrition and administration of chemotherapeutic agents.